Effects of Rodent Diet Choice and Fiber Type on Data Interpretation of Gut Microbiome and Metabolic Disease Research. Issue 1 (20th July 2018) - Pellizzon, Michael A.; Ricci, Matthew R.
Abstract: Poor diet reporting and improperly controlling laboratory animal diet continues to reduce our ability to interpret data effectively in animal studies. In order to make the best use of our resources and improve research transparency, proper reporting methods that include a diet design are essential to improving our understanding of the links between gut health and metabolic disease onset. This unit will focus on the importance of diet choice in laboratory animal studies, specifically as it relates to gut health, microbiome, and metabolic disease development. The two most commonly used diet types, grain‐based (GB) diets, and purified ingredient diets, will each be described, with particular emphasis on their differences in dietary fiber. A further description of how these diet types and fiber can affect gut morphology and microbiota will be provided as well as how purified ingredient diets may be improved upon. © 2018 by John Wiley & Sons, Inc.